Efficacy of alitretinoin in the treatment of Darier disease - Pagon, Andreja (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2023)
Darier disease is a rare autosomal dominant genodermatosis that initially first presents in adolescence with scaly reddish brown keratotic papules and plaques with a seborrheic and intertriginous distribution. The absence of specific targeted medications complicates the treatment process, and managing resistant cases can prove challenging due to recurrent exacerbations that may result in serious complications such as secondary bacterial and viral infections. Treatments of choice include antiseptics, topical corticosteroids, and systemic retinoids, mainly acitretin and isotretinoin. We report the case of a female patient with Darier disease that was unsuccessfully treated with acitretin and isotretinoin but showed significant improvement with alitretinoin. Previous reports on the efficacy of alitretinoin in Darier disease are reviewed.
Keywords: alitretinoin; darier disease; Darierjeva bolezen; genodematoza; genodermatosis; retinoidi; retinoids; sistemsko zdravljenje; systemic treatment